The effectiveness of visualization, auditory, kinesthetic and guided inquiry learning models on students writing skills - Alnovgada, Valents Roni Sunarno (Universitas Muhammadiyah Malang, 2024)
This study focuses on the problem of low writing skills in junior high school students' explanatory texts caused by low reading interest, limited vocabulary, and ineffective Learning models. Therefore, a study is needed to compare the effectiveness of Visualization, Auditory, Kinesthetic (VAK.), and Guide Inquiry Learning (GIL.) Learning models in improving students' writing skills on the topic of actual problems. A quasi-experimental design was used with a pretest-posttest nonequivalent control group design involving Santu Petrus Catholic Junior High School students in the academic year 2023/2024 in Pontianak as the population. The sample of this study included 105 students who were selected using the cluster random sampling method. The data obtained were from students' explanation text writing test results, which were then analyzed using One-Way ANOVA and Scheffe tests. The results showed that the VAK model significantly and more effectively influenced students' explanation text-writing skills than the GIL and DL (conventional) models. Applying the VAK model can be an effective strategy for improving students' writing skills. In addition, the findings guide educators and curriculum developers to design learning that is more responsive and appropriate to students' learning styles. The VAK model allows students to utilize their learning preferences, such as visual, auditory, and kinesthetic, thus creating a more creative and enjoyable learning environment.